Daya Tahan Sektor Rumah Tangga Dalam Rangka Menjaga Stabilitas Sistem Keuangan - Rakhmawati, Ita; Suhadi, Suhadi (BISNIS, 2017)
The crisis in 1997 is the image of the high rise in inflation in Indonesia. The phenomenon of inflation when it reached 82.40% (Anas, 2006). The early mid-1998 also experienced a weakening of the rupiah against the dollar. Condition stable economy is the desire of each country in comparison with the state of the economy has always fluctuated. Economic stability will create an atmosphere conducive economy. stable climatic conditions in the expected level of welfare is the purpose in each country. One of the efforts to maintain economic stability is through monetary policy. For example, with economic growth, maintain price stability (inflation), the achievement of the balance of payments and the reduction of unemployment (Natsir, 2008). The stability of the financial system of a country of which reflected their price stability, in the sense that there are a great price that can be harmful to society, both consumers and manufacturers that will damage the joints of the economy. However, the implementation of the policy, Bank Indonesia as the monetary authority uses monetary variables such as interest rates and the money supply to cope with economic shocks such as inflation. Besides the need for the government’s role in maintaining the rupiah to avoid turmoil in the economy. The importance of inflation control based on the consideration that the high inflation and unstable negative impact on socio-economic conditions of society. Among the high inflation will cause a decline in the real income of the community so that the standard of living of the people down and eventually make everyone, especially the poor get poorer. From one of the effects of inflation are so wide will impact people’s demands to meet the needs of more and more difficult. Their continuousprice increases being offset by rising income of the communities, it can make sure the Indonesian state would worsen. As a result many people’s needs can not be met, so many things that must be met by way of credit. The number of community needs that must be met will cause world of opportunities for banks to offer credit readily available to meet the needs. The third object of research above (inflation, poverty, and credit) does affect the stability of the financial system? In this study using secondary data from the Badan Pusat Statistik (BPS) and Bank Indonesia (BI) with time series data from the years 2007-2015. The process of data analysis was performed using OLS regression with Eviews 8.0. Based on research, if only partial test of the poverty variable significantly affect the stability of the financial system amounted to 2,023 with α = 10%. Meanwhile, two other variables (inflation and poverty) is not significant to the stability of the financial systemMeanwhile, two other variables (inflation and poverty) is not significant to the stability of the financial system. While the value of R-Square (0.629900), indicating that the three independent variables / free consisting of inflation, poverty and credit simultaneously have the effect that make the stabilization of the financial system increases or decreases. That is jointly independent variables (inflation, poverty and loans) contributed / effect of 62.9% against the stability of the financial system. The rest is the influence of other factors beyond the three independent variables studied.